Comorbidity of Narcolepsy and Psychotic Disorders: A Nationwide Population-Based Study in Taiwan - Yeh, Jia-Yin; Shyu, Yu-Chiau; Lee, Sheng-Yu; Yuan, Shin-Sheng; Yang, Chun-Ju; Yang, Kang-Chung; Lee, Tung-Liang; Sun, Chi-Chin; Wang, Liang-Jen (Frontiers in Psychiatry, 2020)
Background: Narcolepsy is a chronic sleep disorder that is likely to have neuropsychiatric comorbidities. Psychotic disorders are characterized by delusion, hallucination and reality impairments. This study investigates the relationship between narcolepsy and psychotic disorders. Design and methods: This study involves patients who were diagnosed with narcolepsy between January 2002 and December 2011 (n = 258) and age- and gender-matched controls (n = 2580) from Taiwan’s National Health Insurance database. Both the patients and the controls were monitored from January 1, 2002 to December 31, 2011 to identify any occurrence of a psychotic disorder. Drugs that have been approved for treating narcolepsy: immediate-release methylphenidate (IR–MPH), osmotic controlled-release formulations of methylphenidate (OROS–MPH), and modafinil, were analyzed. A multivariate logistic regression model was used to evaluate the potential comorbidity of narcolepsy with psychotic disorders. Results: During the study period, 8.1% of the narcoleptic patients exhibited comorbidity with a psychotic disorder, whereas only 1.5% of the control subjects (1.5%) had psychotic disorders (aOR, 4.07; 95% CI, 2.21–7.47). Of the narcolepsy patients, 41.5%, 5.4% and 13.2% were treated with MPH-IR, MPH-OROS and modafinil, accordingly. Pharmacotherapy for narcolepsy did not significantly affect the risk of exhibiting a psychotic disorder. Conclusions: This nationwide study revealed that narcolepsy and psychotic disorders commonly co-occur. Pharmacotherapy for narcolepsy was not associated with the risk of psychotic disorders. Our findings serve as a reminder that clinicians must consider the comorbidity of narcolepsy and psychosis.